Characterization of a Norovirus‐specific monoclonal antibody that exhibits wide spectrum binding activities. Issue 4 (4th January 2018) - Zheng, Lijun; Wang, Wenhui; Liu, Jinjin; Chen, Xuhui; Li, Sanjing; Wang, Qiaoli; Huo, Yuqi; Qin, Chuan; Shen, Shuo; Wang, Mingchen
Abstract : Noroviruses (NoVs) are increasingly recognized as the leading cause of acute non‐bacterial gastroenteritis worldwide. To screen for NoV‐specific monoclonal antibodies (mAbs) with wide spectrum binding activities that could be used for the development of NoV‐related detection reagents, we immunized mice with a combination of virus like particles (VLPs) derived from eight different genotypes (two from genogroup I and six from genogroup II), of which two (GI.7 and GII.2) were newly produced VLPs. Indirect enzyme‐linked immunosorbent assay (ELISA) confirmed that two mAbs (8D8 and 10B11) bound to all eight major capsid proteins (VP1) with varied binding abilities. Epitope mapping using short peptides covering the N‐terminal half of GII.3 VP1 indicated that the binding site of mAb 8D8 was located between amino acid 31 and 60. Multiple amino acid sequence alignment of VP1 suggested that this site harbors conservative sequences across all genogroups. Indirect and sandwich ELISA indicated that mAb 8D8 was unable bind intact VLPs. In summary, we successfully produced GI.7 and GII.2 VLPs using recombinant baculovirus expression system and a cross‐reactive mAb by immunizing mice with eight different VLPs that might be useful in the studying and detecting NoVs.